Pemilu dan Pilkada dalam Pusaran Politik Identitas - Eka Putra B Santoso (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
The relationship between politics and religion in Indonesia at this time can be seen from one important thing that is being popularly known, namely politics of identity. Politics of identity is the main spotlight in politics in Indonesia, especially in mainstream and non-mainstream media such as social media. The word politics of identity today can be said to have the same